The finite element method : a practical course - Liu, G. R.; Quek, S. S. (Butterworth-Heinemann, 2003)
The Finite Element Method (FEM) has become an indispensable technology for the modelling and simulation of engineering systems.Written for engineers and students alike, the aim of the book is to provide the necessary theories and techniques of the FEM for readers to be able to use a commercial FEM package to solve primarily linear problems in.